Hubungan masyarakat sebagai strategi membangun kepercayaan publik di lembaga keuangan syariah non-bank - Rahma, Anida Salsabila (Maliki Interdisciplinary Journal, 2025)
Public relations play an essential role in building a positive image and public trust toward Islamic non-bank financial institutions. This study aims to analyze public relations strategies in strengthening communication with the community through Islamic values such as honesty, transparency, justice, and trustworthiness. The research uses a descriptive qualitative method by reviewing various literatures, scientific journals, and reports from Islamic non-bank financial institutions. The results show that the success of these institutions is strongly influenced by the effectiveness of public relations in creating two-way communication aligned with Sharia principles and public needs. Public relations are not merely a promotional tool but also an educational medium that enhances Islamic financial literacy and fosters stronger public trust.